Penerapan Bimbingan Kelompok dengan Metode Problem Based Learning untuk Meningkatkan Kedisiplinan Belajar Peserta Didik di SMPN 7 Palembang - Dila julianti; Amrina Jaya; Fadhlina Rozzaqyah (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
Learning discipline is an essential factor in supporting students' academic success. However, many students still show a lack of awareness in managing their study time and completing assignments on time. This study aims to determine the effectiveness of implementing group counseling using the Problem-Based Learning (PBL) method to improve students’ learning discipline at SMP Negeri 7 Palembang. This research employed an action research design with a cyclical model consisting of planning, implementation, observation, and reflection stages. The research subjects were eight ninth-grade students selected through purposive sampling. Data were collected using pretest and posttest in the form of multiple-choice questions to assess time management understanding. The results showed an increase in the average score from 50 (pretest) to 88.75 (posttest). The N-Gain analysis result of 0.79 (79.23%) indicates that the implementation of group counseling with the PBL method is highly effective in improving students’ learning discipline. Therefore, this approach can be an alternative solution to address learning discipline issues in schools.